PERAN UMKM DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Elvina Riska; Liza Nurlaila (CV. ADIBA AISHA AMIRA, 2024)
This study is a study using literature research or literature review method. A literature review is a comprehensive overview of research conducted on a specific topic, designed to show the reader what is known and unknown about the topic, to find justification for research that has been conducted, or to find ideas for previous research. Some time ago, many large companies in our country experienced slowed growth or even closed due to the economic crisis. Meanwhile, the micro, small and medium enterprise sector has demonstrated its ability to survive and develop despite the economic crisis. Given what we learned during the crisis in Indonesia, it makes sense that private sector economic growth efforts are concentrated on MSMEs